Implementation Of Instructional Leadership By School Principals In Elementary School - Nikmah, Nurun; Lailiyah, Muhimatul; Nurkolis (Institut Agama Islam Negeri (IAIN) Curup, 2025)
This study explores the influence of school principals' instructional leadership on teacher performance and student learning outcomes at SD Negeri Gilis, Sarang District, Rembang Regency. The approach used in this research is descriptive qualitative, with data collection techniques including interviews, observations, and document studies. The results show that implementing the principal's instructional leadership plays a crucial role in improving the quality of lesson planning carried out by teachers. Although initially there were challenges related to the misalignment in the lesson plan preparation by most teachers, the principal's strategies, which included enhancing the quality of lesson planning, need-based academic supervision, and empowering teachers through the Teacher Working Group (KKG), successfully addressed these issues. After three months of implementation, 90% of teachers could prepare lesson plans aligned with the Merdeka Curriculum, and teacher involvement in KKG discussions significantly increased. Furthermore, time management and teaching methods in the classroom also showed improvements. This study concludes that well-planned instructional leadership by the principal, based on teacher professional development, can enhance the quality of teaching and positively impact student learning outcomes. Recommendations for further development include improving the principal's competence in academic supervision and utilizing technology in teaching.